Applying Cognitive-Behavioral Therapy to Help Survivors of Dating Violence: A Pilot Study - Stefanus Perangin-Angin; Sutarto Wijono; Arianti Ina Restiani Hunga (Jurnal Psikologi, 2021)
Research from National Commission on Elimination of Violence against Women found that dating violence was ranked second after domestic violence in terms of number of cases reported in 2018 in Indonesia. Post-Traumatic Stress Disorder (PTSD) was one of the consequences that dating violence survivors experienced. Cognitive-Behavioral Therapy (CBT) had been proven effective to treat PTSD in intimate partner violence survivors. However, there was no prior research publication investigating the effectiveness of CBT for dating violence survivors in Indonesia. This research aimed to apply CBT to help treating PTSD symptoms in women with dating violence experiences. CBT was delivered individually for six sessions to four participants. This research used mixed-method design with quantitative and qualitative data collection and data analysis components. PTSD Checklist for DSM-5 was used to measure PTSD symptoms at pre- and post-treatment. The results showed that all participants had reduction in PTSD symptoms at post-treatment. However, two participants still met the criteria for PTSD because their post-treatment scores were still above remission cut-off scores. Future research can focus on helping survivors to gain resiliency, psychological well-being, self-esteem and regaining meaning of life back after having dating violence experiences.